MORPHOTYPIC STRUCTURE OF HONEY BEES AND THEIR MORPHOLOGICAL CHANGES - Semenov, V.G.; Skvortsov, A.I.; Sattarov, V.N.; Baimukanov, D.A.; Doshanov, D.A.; Karibayeva, D.K. (Scientific Journal of Pedagogy and Economics, 2020)
One of the key aspects of the preservation of endemic populations of modern honey bee breeds is research in the identification of their morphological characters in apiaries, as an assessment of the cleanliness of queen bees and the potential for restoration of populations. The research material was a sampling of summer generation bees. The volume amounted to 640 individuals from 16 bee families in three districts of the forest-steppe and steppe honey flow areas (Margaushsky (3 families - apiary of the K.I.Michurin farm firm), Krasnoarmeysky (6 families from Pchelovodcheskoe OOO) - forest-steppe zone; Batyrevsky district (7 families from Pirozhkova N.P. farm) - steppe honey flow area). The assessment was carried out according to the common method, during which 15 traits were measured. The studies of the morphotypic structure of honey bees revealed the dominant conformity of the identified classes of workers and drones to the standard of the Central Russian subspecies. The research results showed that the morphotype of working bees is represented by the prevailing class - O and the minimum represented - 1R. The drones morphotype is represented only by class O. At the same time, a complex methodology, including an analysis of the "purity" of working bees and drones, allows us to note the genetic safety, both on the maternal lineage and the paternal side, respectively. However, studies of morphological abnormalities in Apis mellifera revealed eye color changes only in drones, namely brown or pomegranate and white eyes. The studies have revealed the potential for preservation of the population of the European dark (Central Russian) bee breed in Chuvashia. The decrease in the minimum tergite value recorded in the Morgaushsky district beyond the standard frames of the Central Russian breed does not indicate the ongoing hybridization processes since this is the only one and can be explained by some random factors affecting biophysiological processes.